Kepunahan Bahasa Dalam Aspek Sosiolingustik - Mahfud Saiful Ansori (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
Language extinction Is a total shift in one language and that shift from one language to another, not from one language to another in one language, meaning the first language that was originally used by a speech joint (community language users become extinct because the speech jokes favor second languages (totally leaving their first language), or because the disappearance of the language user community that occurs due to natural disasters and such. Because many things cause the extinction of a language, namely there are four: First, the speakers think of themselves as socially inferior. Second, attachment to the past. Third, the traditional and Fourth side, because economically life is stagnant. But apart from all that, there are also efforts that can be made to prevent and prevent the extinction of language through the inculcation of awareness of language preservation, including local language subjects at every level of education.